Nursing teaching in mental health: focus on group technology (Research, Society and Development, 2021)
Objective: to describe the experience of using group technology in teaching mental health for Nursing, from the perspective of teachers. Method: this is an experience report, developed in 2018 at a public university in the central region of Brazil, of a descriptive nature and made by professors. In this sense, the pedagogical strategy of the Mental Health discipline was based on the principles of Laboratory Education and the learning resources used prioritized group activities in nine meetings of the discipline. In addition, the information analyzed was contained in the field diaries used by the professors to support the process of evaluating the group strategies that took place during the planning meetings, at each class, during classes and at the end of the course. Results: the group technology resources used were described by the professors who observed and reported awareness of changing students' attitudes, focusing on the principles of the helping relationship in Nursing interventions, expanding self-confidence and self-discovery, consequently, interpersonal competence in the relationships undertaken. Conclusion: the group experiences throughout the course made it possible to highlight the potential of group technology for teaching mental health from the perspective of understanding human interactions and reflecting on the elements related to the maintenance of people's mental well-being.